EXPRESSION OF RESPECT IN LITERATURE OF DIFFERENT SYSTEMIC LANGUAGES (TAMADDUN NURI JURNALI, 2025)
This article explores the linguistic and cultural expressions of respect in English, Uzbek, and Russian. By analyzing traditional form of respect in various literatures, it highlights how these expressions reflect social values and cultural priorities. Drawing from classic and contemporary works such as “Pride and Prejudice”, “O‘tkan kunlar”, and “War and Peace”, the article delves into the unique ways respect is communicated in each language. This comparative study fosters a deeper understanding of cross-cultural communication.